STRATEGI PIMPINAN DALAM MENGELOLA SARANA DAN PRASARANA DI STAIN TEUNGKU DIRUNDENG MEULABOH - Herman, Herman; Ayuningtyas, Dian; Riska, Riska (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
Facilities and infrastructure are one of the most important components to support academic and non-academic activities. This study aims to determine the leadership strategy in managing facilities and infrastructure at STAIN Teungku Dirundeng Meulaboh. The type of research used here is qualitative research, with data collection methods through observation, interviews and documentation studies. Data processing and analysis techniques through the stages of data reduction, data presentation, and verification (Conclusion Drawing). The results showed that the leadership strategy in managing facilities and infrastructure at STAIN Teungku Dirundeng Meulaboh was carried out through strategies: 1) budget preparation planning work meetings involving leadership elements, and the planning process refers to the RIP, RPJM, and RPJP documents, 2) setting schedules, and local committee for procurement of sarpras and coordinating with the procurement committee of Kemenag RI for the process of implementing sarpras procurement, 3) conducting inventory, and deletion, and 4) supervision of sarpras by the Internal Supervisory Unit (SPI) as the party appointed and responsible for overseeing the procurement process and financial expenditure for infrastructure needs.